Folk Wisdom of a Lanna Music Teacher: A Study on Mr. Boonlert Teekang - Sankam-ai, Chanidapa; Srisombut, Rujee (Fine Arts Journal: Srinakharinwirot University, 2015)
This research aims to study; one, the history and folk wisdom of Lanna music of Mr. Boonlert Teekang, and; two, Tuengnong drum bands in relation with traditions, rituals, and shows. From the study of the information that wasobtained from surveys, interviews, and data analysis; it was revealed that: 1. Mr. Boonlert Teekang is an experienced man in local Lanna music and is well accepted among local Lanna musicians in Chiang Mai province. Moreover, he is a lecturer who has knowledge about the production of the Aaw drum, or Tuengnong drum, and has the ability to play various local music instruments. In addition, he made the Aaw drum that had the best sound and gained acceptance from people during the Aaw drum competition held in Chiang Mai, and received the award “Pet Rajabhat” from Chiang Mai Rajabhat University. Mr. Boonlert is considered as a person who continues and preserves the knowledge of making Aaw drums, which he received from Master Dumrong Chaipet, who once was the father of Lanna drums who passed away years ago. 2. Tuengnong drum bands:Tuengnung, or Tuengnong, drum is the name of a type of drum namedafter the sound when played together with a big gong, Hui gong, and other instruments, such as cymbals, Talodpod drum, Naeluang, and Naenoi (similar to clarinet). This combination is called “Tuengnongband,” in which the Aaw drum makes the sound of “Tueng” and “Yong,” and the Hui gong makes thesound of “Nung” or “Nong”. Tuengnong drum band is played on various occasions, such as a meritparade to the temple, religious buildings celebration, and other entertainment events. As mentioned above, the Tuengnong drum band has a unique melody and sound which plays an important role inLanna community for a long time. Furthermore, Aaw drums or Tuengnong drums can also be played together with Talodpod, Yong gong, Hui gong, and Sawa, and are usually played druing merit events andused as a background music for the finger-nails dancing, one of the famous northern traditional dancing styles, performing for welcoming guests. The Aaw drum has been developed since the Mungray dynasty,which the drum appearance was similar to Singmong drum, Pujaedrum, and Luang drum, and it wascalled differently in different areas. In order to make Aaw drums, there are many rituals involved such asthe ceremony of cutting the wood and making drumhead, and paying respect to the spirit and teacher. Inaddition, people who are involved in Aaw drums, they carry on the belief of good luck and bad luck day,as well as the belief of drum luck, which is rooted from religious belief and the folk wisdom of ancestors, which have been carried on for ages.